Social perceptions of marital violence - Casimiro, Cláudia (2002)
Perceptions of marital violence vary according to the social class involved. Under-privileged women associate violence with physical force while in the better-off social groups the psychological aspect is emphasized. Tolerance to violence is higher in women with lower levels of education working in less-qualified jobs, while the inverse is true among women with higher levels of education and general culture.